Reformas al procedimiento especial para contravenciones de tránsito, estipulado en el Código Orgánico Integral Penal - Noguera Chacón, Elizabeth Mariuxi (2016)
The recently approved Code Organic Penal Integral, material expression of the Ecuadorian positive Criminal law that has as purpose according to their article 1, normar the punitive power of the State, tipificar the penal infractions, to establish the procedure for the trial of people and to promote the social rehabilitation of sentenced people and the integral repair of the victims, creó in the book second that talks about the penal adjectival procedure, the special procedures for the smallest trials of crimes whose pain doesn't exceed of 10 or 5 years, depending on the case. These procedures are: the abbreviated one, the direct one, the expedite one and the procedure for the private exercise of the action. The foundation of the same ones, is to give bigger velocity and agility to the administration of penal justice, with terms courts in those that should be made the trial audiences, but this velocity, in many of the cases doesn't allow the offender to exercise its right to the defense with the time and the opportunities that it allows him the Constitution of the Republic. It is the case of the expedite special procedure for traffic breaches, same that in their rules settled down in the Código Orgánico Integral Penal, it restricts constitutional laws to the same one and the self-defense, everything that when an offender is mentioned in a different place and very far from his home, he won't have the same time that another to prepare his defense, or in the worst in the cases, he will not even have the opportunity to return to refute his citation; another case is the restriction to appeal the sentences in this type of infractions, because the Coding Organic Integral Penal only allows to appeal the shortcomings, when they are restrictive to the freedom, in this sense. This work seeks to demonstrate the normative falencias that exist in the special procedure for traffic infractions